Microbiological evaluation of meat sold in butcheries shop of Cheleleka town in anchar woreda, West Harerge, Oromia, Ethiopia Western Ethiopia - Wazir Shafi Mustefa (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2021)
Food borne infections and disease are a main international health problem with consequent economic loss and deaths. Meat is considered the most vital source of proteins consumed by humans, so far, most perishable. For highly consumable foodstuffs such as fresh red meat, the hazard of food poisoning is mainly high since it contains all the nutrients that support bacterial growth. The objective of the study was evaluated bacteriological meat quality sold in shops of Cheleleka town in west harerge zone, Oromia region, Ethiopia. Samples of kitfo and gored-gored were collected from five different meat shops. The microbial quality of raw meat sold in five most popular meat shops in the of Cheleleka Town was determined to ascertain its safety. The meat samples were taken from Genet, Wondu, Ayichuluhum, Alemayehu, and Kamil shops. A total of 10 raw meat samples were collected in two successive visits. Raw samples from Ayichuluhum had the highest mean total aerobic bacterial count of 3.3 × 106 cfu/g for kitfo and 2.8 x 106 cfu/g for gored-gored. The lowest counts were obtained from Genet (7.8 × 105 cfu/g and 7 x 105 cfu/g) for Kitifo and Gored-gored were recorded respectively. The highest mean fecal counts (2.0 × 106 cfu/g for kitfo and 1.7 × 106 cfu/g for gored-gored) were obtained also from Ayichuluhum shop. From Genet shop was seen the lowest fecal coliform bacterial counts of 4.3 × 105 cfu/g for Kitifo and 4 × 105 cfu/g for gored-gored. Bacterial species isolated from the samples were mostly Gram-positive rods and Gram-positive spherical bacteria in clumps. Some Gram-negative rods were also seen some of which may be fecal coliforms. The high bacteria count and diversity of bacterial isolates from the samples tested is an indication of its low bacteriological quality, and this can make it a potential source of food infection.